Trending Fibrinolytic Dysregulation: Fibrinolysis Shutdown in the Days After Injury Is Associated With Poor Outcome in Severely Injured Children. Issue 3 (September 2017) - Leeper, Christine M.; Neal, Matthew D.; McKenna, Christine J.; Gaines, Barbara A.
Abstract : Objective: To trend fibrinolysis after injury and determine the influence of traumatic brain injury (TBI) and massive transfusion on fibrinolysis status. Background: Admission fibrinolytic derangement is common in injured children and adults, and is associated with poor outcome. No studies examine fibrinolysis days after injury. Methods: Prospective study of severely injured children at a level 1 pediatric trauma center. Rapid thromboelastography was obtained on admission and daily for up to 7 days. Standard definitions of hyperfibrinolysis (HF; LY30 ≥3), fibrinolysis shutdown (SD; LY30 ⩽0.8), and normal (LY30 = 0.9–2.9) were applied. Antifibrinolytic use was documented. Outcomes were death, disability, and thromboembolic complications. Wilcoxon rank-sum and Fisher exact tests were performed. Exploratory subgroups included massively transfused and severe TBI patients. Results: In all, 83 patients were analyzed with median (interquartile ranges) age 8 (4–12) and Injury Severity Score 22 (13–34), 73.5% blunt mechanism, 47% severe TBI, 20.5% massively transfused. Outcomes were 14.5% mortality, 43.7% disability, and 9.8% deep vein thrombosis. Remaining in or trending to SD was associated with death ( P = 0.007), disability ( P = 0.012), and deep vein thrombosis ( P = 0.048). Median LY30 was lower on post-trauma day (PTD)1 to PTD4 in patients with poor compared with good outcome; median LY30 was lower on PTD1 to PTD3 in TBI patients compared with non-TBI patients. HF without associated shutdown was not related to poor outcome, but extreme HF (LY30 >30%, n = 3) was lethal. Also, 50% of massively transfused patients in hemorrhagic shock demonstrated SD physiology on admission. All with HF (fc31.2%) corrected after hemostatic resuscitation without tranexamic acid. Conclusions: Fibrinolysis shutdown is common postinjury and predicts poor outcomes. Severe TBI is associated with sustained shutdown. Empiric antifibrinolytics for children should be questioned; thromboelastography-directed selective use should be considered for documented HF.